Profit Allocation in the Turkish Electricity Industry Based on Cooperative Game Theory - Ertemel, Sinan; Karaca, Nurtac (Springer International Publishing, 2020)
In this paper, the retail electricity supply to the end-user electricity customers is studied via cooperative game theory. There are two major players in the retail electricity market in Turkey: power plants and retailers. Players with retail licenses, who sell retail electricity directly to the end-user, operate with very low levels of profit margin due to high cost and competition in the market. On the other hand, power plants have a generation capacity, yet they lack sales and marketing know-how compared to retailers. We show that when power plants and retailers cooperate and integrate the market vertically, they can generate more profit compared to stand-alone. Accordingly, we investigate profit-sharing among these players using cooperative game theory. To this end, we choose Nash Bargaining, Kalai-Smorodinsky Bargaining, and weighted Shapley solutions and compare their results.